Multi-step enzyme reaction in an Immobilized Enzyme Microreactor (IEMR) - Abdul Halim, Amanatuzzakiah; Baganz, Frank (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
The application of biocatalyst in microfluidic systems has attracted huge attention in recent years due to their potential for creating microscale analytical tools with small volumes, high-throughput and attractive prospect for mass production. This system can be integrated with the multi-step enzyme reaction to synthesize complex organic compounds such as a single diastereoisomer of 2-amino-1,3,4-butanetriol (ABT). ABT is an interesting compound, commonly used as the building block in several pharmaceutical syntheses. In this work we study a de novo designed pathway for the production of ABT using IEMRs, which is based on the reversible attachment of His6-tagged enzymes via Ni-NTA agarose beads that are packed into tubes to enable continuous flow of multi-step enzyme reactions. The synthesis of ABT was demonstrated in a three-step enzyme reaction using two enzymes; transketolase and transaminase. In the first part of the three-step reaction, His6-TAm catalysed the conversion of the substrates, serine (SER) and glycoaldehyde (GA), to form lithium-hydroxypyruvate (HPA). The product of the first reaction was then continuously fed to the second IEMR containing the immobilized His6-TK, which catalysed the reaction between HPA and GA into erythrulose (ERY). The multi-step reaction was completed with the amination of ERY by the second His6- TAm to produce the final target product, ABT.